Menjajaki Kemungkinan Islamisasi Sosiologi Pengetahuan - Muhammad Imdad (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2015)
In the discussion of epistemology, the study of objectivity led to the disciplines of sociology. The principal thesis of the sociology is that there are modes of thought which cannot be adequately understood as long as their social origins are obscure. In its association with the project of Islamization of contemporary knowledge initiated by Syed Muhammad Naquib al-Attas, sociology turns out supporting one of the basic assumptions of this project; whereas science has their own value (value laden). In al Attas’s view, science has worldview, intellectual vision, and psychological perception which play a key role in interpretation, formula, and deployment of knowledge understood in perspective of certain civilization. It means, any knowledge that is read and then developed by particular civilization, will be loaded with values constituted that civilization. When we get that sociology came from Western civilization could not be separated from the burden of civilization accompanying it, worldview approach will be most appropriate to trace back and explain Islamization of sociology of knowledge. One of figures that has a close view with sociology of knowledge is Karl Mannheim, with his theory of Relationism. Mannheim’s keywords are ideology in the form of concept born from political conflict, and the utopia which is the opposite of the ideology mentioned in the form of intellectually oppressed group who wanted social change. This paper is going to elaborate possibilities of Islamization of sociology, the theory of Relationism presented by Karl Mannheim. This study concludes that Relationism is same with relativism and different from Islamic worldview conceptually.